Plasma B-type Natriuretic Peptide (BNP) as a marker of left ventricular diastolic dysfunction in diabetic patients (Ibrahim Medical College Journal, 2015)
The first stage of diabetic cardiomyopathy is represented by left ventricular diastolic dysfunction (LVDD) with preserved systolic function, in an asymptomatic patient. B-type Natriuretic Peptide (BNP) is a cardiac neurohormone predominantly released from the cardiac ventricles in response to left ventricular volume expansion and pressure overload. The diagnostic role of BNP for detecting LVDD in asymptomatic diabetic patients is still debated and this study was undertaken to find out this relationship of plasma BNP level with LVDD in asymptomatic diabetic patients. First 100 patients who had type 2 diabetes for more than 5 years and had no known cardiac disease other than LVDD (grade-1 & 2), admitted in BIRDEM Hospital were recruited. Plasma BNP was measured by fluorescence polarization immunoassay (FPIA) method using AXSYM auto analyzer. Twodimensional, M-mode, spectral, and color flow Doppler echocardiograms was repeated on the same day of blood collection for plasma BNP measurement. After processing of all available data, statistical analysis of their significance was done with the help of computer based SPSS (Statistical Program for Social Science) program. Male female distribution of the study participants was 46% and 54% respectively. Mean plasma BNP level in all participants was 150 pg/ml. In male and female participants the values were 168 and 135 pg/ml respectively. The distribution did not show any significant association (p=0.491). Of the 100 study participants 89% had E/A ratio